Application Research of Public Art in the Design of Old People's Rehabilitation Space Based on Virtual Information Interaction Platform From the Perspective of Developing Economies - Zhang, Shaoqing (Frontiers in Public Health, 2022)
In order to solve the problem of the design of the old people's recuperation space, the virtual information interaction platform was used to study the public art application in the design of the old people's recuperation space. Existing geriatric institutions were investigated. Under the premise of optimizing the function of the facility, the concept of human care, emotional care and humanization in public art is integrated into the design of the elderly rehabilitation space. In addition, this was also an important part of building a harmonious society to promote the humanized design of public art in the elderly rehabilitation space. The old people’s negative impression of the long-standing depression and indifference of the old-age maintenance institutions was resolved. In the modern elderly rehabilitation space, the emphasis and application of public art design inevitably brought spiritual and material life help to the old people's later life, and created a happy, serene and comfortable old age life for them. The results showed that the recuperation space design was built according to the needs of different old people, which helped the old people to eliminate loneliness and enhance the value of the old people. Therefore, the old people can also make life full of joy and meaning.